Vascular complications of the eye in the late postpartum period of postponed preeclampsia - O. V. Кolenko; E. L. Sorokin; A. A. Fil; N. V. Pomytkina (Офтальмохирургия, 2020)
The article presents the main pathogenetic mechanisms of endothelial dysfunction formation in complicated pregnancy and vascular pathology. The possible consequences of postponed preeclampsia are described. The performed analysis of the literature allows to approve that preeclampsia should be considered as a pathology threatening an increased risk of the vascular eye pathology formation, both in the short and in the long-term periods after childbirth.